2021
DOI: 10.1039/d1dt01189h
|View full text |Cite
|
Sign up to set email alerts
|

Cu boosting the collaborative effect of Ni and H+ in alloyed NiCu/saponite catalysts for hydrogenolysis of glycidol

Abstract: The effect of copper on various acid saponite supported Ni-Cu bimetallic catalysts, prepared with different Ni:Cu ratios, was studied for the liquid phase hydrogenolysis of glycidol on a batch reactor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“… 30 Here, the metal/oxide interface, the synergy between Cu 0 sites and −OH groups, and basic Lewis sites shape the overall catalyst activity and selectivity. 31 , 32 For example, in the case of Cu/ZnO/ZrO 2 catalysts, hydrogen adsorption and dissociation are carried out by Cu sites. The basic sites of ZnO and ZrO 2 are responsible for CO 2 adsorption (as a mixture of carbonate and bicarbonate species).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Here, the metal/oxide interface, the synergy between Cu 0 sites and −OH groups, and basic Lewis sites shape the overall catalyst activity and selectivity. 31 , 32 For example, in the case of Cu/ZnO/ZrO 2 catalysts, hydrogen adsorption and dissociation are carried out by Cu sites. The basic sites of ZnO and ZrO 2 are responsible for CO 2 adsorption (as a mixture of carbonate and bicarbonate species).…”
Section: Introductionmentioning
confidence: 99%
“…Copper is another transition metal considered for hydrogenation reactions both as (1) a Cu-based catalyst with a high specific surface area and semiconductor properties (usually up to 60–70% Cu content), i.e., Cu–ZrO 2 and Cu/ZnO/ZrO 2 for the CO 2 -to-methanol reaction, and (2) Cu complexes, i.e., copper­(I) complex LCu­(MeCN)­PF 6 for CO 2 hydrogenation to formate/formic acid in the presence of DBU as the base. , Applying higher pressure, usually 5–40 atm, supported Cu-based catalysts being used in various industrially relevant hydrogenation processes, i.e., methanol synthesis, the low-temperature water–gas shift, and various organic compounds’ selective hydrogenation or fine chemical synthesis . Here, the metal/oxide interface, the synergy between Cu 0 sites and −OH groups, and basic Lewis sites shape the overall catalyst activity and selectivity. , For example, in the case of Cu/ZnO/ZrO 2 catalysts, hydrogen adsorption and dissociation are carried out by Cu sites. The basic sites of ZnO and ZrO 2 are responsible for CO 2 adsorption (as a mixture of carbonate and bicarbonate species).…”
Section: Introductionmentioning
confidence: 99%
“…The same group, investigated a Ni-Cu alloy based catalytic system and observed that the presence of an appropriate amount of Cu allowed the control of the hydrogenation capacity of Ni favouring the formation of 1,3-propanediol [44]. Recently, Sun et al[45] developed a carbon film encapsulated Co nanoparticle catalyst for glycidol hydrogenolysis to 1,3-PD characterized by high productivity and selectivity towards 1,3-PD (50,4% of 1,3-PD obtained at 140 °C, 2 MPa H 2 and 4 h).…”
mentioning
confidence: 99%